2007
DOI: 10.5367/000000007781497746
|View full text |Cite
|
Sign up to set email alerts
|

Research Report: The Lingering Effect of Colonialism on Tourist Movements

Abstract: This short study examines the lasting effects of colonial ties on tourist movements between nations and their current and former possessions. The study examines 56 jurisdictions in six geographical regions that were once colonies of or remain the possessions of eight nations. Residents of Europe and America show a preference for travel to destinations with strong historical/political ties and an equally strong aversion to travel to jurisdictions where no such connection exists. Likewise, destinations rely heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…In a useful discussion of the role that colonialism has played in tourism movements, McKercher and Decosta () observed that in the tourism literature, the discussion of colonialism has been restricted to three contexts: the inclusion of colonialism as a factor in economic development particularly in small island nations (Milne, ; McElroy, , in McKercher and Decoster, 2007), the perpetration of historical colonial relations as a form of neocolonialism (Britton, ; Abbink, ) and the role of tourism in reinforcing the master–servant relationship of the past. As McKercher and Decoster (2007) observed, the broad coverage of the role of colonialism has not been included as a variable in the analysis of post‐colonial tourism flows.…”
Section: Colonialism and Bilateral Tourism Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…In a useful discussion of the role that colonialism has played in tourism movements, McKercher and Decosta () observed that in the tourism literature, the discussion of colonialism has been restricted to three contexts: the inclusion of colonialism as a factor in economic development particularly in small island nations (Milne, ; McElroy, , in McKercher and Decoster, 2007), the perpetration of historical colonial relations as a form of neocolonialism (Britton, ; Abbink, ) and the role of tourism in reinforcing the master–servant relationship of the past. As McKercher and Decoster (2007) observed, the broad coverage of the role of colonialism has not been included as a variable in the analysis of post‐colonial tourism flows.…”
Section: Colonialism and Bilateral Tourism Flowmentioning
confidence: 99%
“…However, post‐colonial tourism flows between colonizer and colonized has been largely neglected although many colonized nations were forced to resort to violence to achieve independence. This is surprising, given the importance of the decolonization process that has seen the emergence of over 100 new nations since 1945 (McKercher and Decosta, ). Rapid decolonization commenced after World War II (1939–1945) and did not conclude until the breakup of the former USSR in 1991.…”
Section: Introductionmentioning
confidence: 99%
“…Given that “international” tourists visiting these territories from the de facto metropole should be classified as domestic tourists, the following analysis recalculates the UNWTO‐published international tourist arrivals removing those tourist arrivals where tourists from the sovereign state arrive into the territories, dependencies, free associations, and special administrative regions and vice versa. Considering that even independent former colonies remain major destinations for residents of the former metropole (McKercher & Decosta, ), counting visitor arrivals from the metropole to dependent territories is not only inaccurate but also misleading in terms of the extent to which the dependent territory is appealing to tourists. The main data source for the international tourist arrivals is the UNWTO's (, , ) Yearbook files by destination for the period 1995 to 2014.…”
Section: International Tourism Versus Domestic Tourismmentioning
confidence: 99%
“…Colonial ties are explored as a facilitator of tourism flows by McKercher and Decosta (2007). The authors note that lingering effects of colonization can remain strong, especially in the case of French and Dutch tourists.…”
Section: Literature Reviewmentioning
confidence: 99%